Hypoxia enhances the viability, growth and chondrogenic potential of cryopreserved human adipose-derived stem cells - Wan Kamarul Zaman, Wan Safwani; Choi, Jane Ru; Yong, Kar Wey; Ting, Iris; Mat Adenan, Noor Azmi; Pingguan-Murphy, Belinda (Elsevier, 2017)
Cryopreservation is the only existing method of storage of human adipose-derived stem cells (ASCs) for clinical use. However, cryopreservation has been shown to be detrimental to ASCs, particularly in term of cell viability. To restore the viability of cryopreserved ASCs, it is proposed to culture the cells in a hypoxic condition. To this end, we aim to investigate the effect of hypoxia on the cryopreserved human ASCs in terms of not only cell viability, but also their growth and stemness properties, which have not been explored yet. In this study, human ASCs were cultured under four different conditions: fresh (non-cryopreserved) cells cultured in 1) normoxia (21% O2) and 2) hypoxia (2% O2) and cryopreserved cells cultured in 3) normoxia and 4) hypoxia. ASCs at passage 3 were subjected to assessment of viability, proliferation, differentiation, and expression of stemness markers and hypoxia-inducible factor-1 alpha (HIF-1α). We found that hypoxia enhances the viability and the proliferation rate of cryopreserved ASCs. Further, hypoxia upregulates HIF-1α in cryopreserved ASCs, which in turn activates chondrogenic genes to promote chondrogenic differentiation. In conclusion, hypoxic-preconditioned cryopreserved ASCs could be an ideal cell source for cartilage repair and regeneration.